Cu2ZnSnSe4 solar cells with 10.6% efficiency through innovative absorber engineering with Ge superficial nanolayer. (6th July 2016) - Giraldo, Sergio; Thersleff, Thomas; Larramona, Gerardo; Neuschitzer, Markus; Pistor, Paul; Leifer, Klaus; Pérez‐Rodríguez, Alejandro; Moisan, Camille; Dennler, Gilles; Saucedo, Edgardo
Abstract: In our recently published work, the positive effect of a Ge nanolayer introduced into the processing of Cu2 ZnSnSe4 absorbers (CZTSe) was demonstrated. In this contribution, the complete optimization of this new approach is presented for the first time. Hence, the optimum Ge nanolayer thickness range is defined in order to achieve an improved performance of the devices, obtaining a record efficiency of 10.6%. By employing this optimized approach, the open‐circuit voltage ( V OC ) is boosted for our pure selenide CZTSe up to 489 mV, leading to V OC deficit among the lowest reported so far in kesterite technology. Additionally, two important effects related to the Ge are unambiguously demonstrated that might be the origin of the V OC boost: the improvement of the grain size and the corresponding crystalline quality, and the interaction between Ge and Na that allows for dynamic control over the CZTSe doping. Finally, evidences pointing to the origin of the deterioration of devices properties for large Ge concentrations are presented. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Ge doping optimization in Cu2 ZnSnSe4 kesterite is presented, demonstrating the ideal concentration range for achieving high‐efficiency photovoltaic devices. Using the optimum amount of Ge, open‐circuit voltages up to 489 mV are obtained, leading to one of the lowest V OC deficits reported for this material. The importance of Ge–Na interaction for the doping level control is also demonstrated.